The Enduring Effect of the British Imperial Policies on South Africa - Miss SOULEF AICHOUCHE, Miss MINATUE EMBOIRIK SAMBA (My University, 2018)
Abstract This work highlights an important historical event, the colonization of South Africa by the British who settled there at the beginning of the 18th century with the intention to civilize and Christianize the indigenous people. But in fact, and with the discovery of gold and diamond, they dehumanized them from their vital rights when they applied their cleavage imperial policies which deeply affected the nation politically, socially, economically and culturally. British rulers formed a white government that represented Britain in its drastic measures-Hence many coercive illegal laws were implemented on the blacks in their working places, in schools, in factories and in their health system. The most marking traits were Segregation and Apartheid which were considered the landmarks in the South African history because the Africans who thought that they gained independence, had found themselves struggling a long term discrimination age of apparent and racial seclusion.